CRITICAL REVIEW ON INDONESIA'S DRAWBACKS AS A PREFERABLE SEAT OF ARBITRATION - Setyawati, Setyawati (Indonesia Law Review, 2013)
Indonesia as a developing country is in the urgent need to improve its arbitration law and practice. One of the reasons is because Indonesia may gain many advantages by such improvement, such as: increase of its international reputation as a safe place to invest or conduct trading since there is an assurance that future disputes may be promptly solved through arbitration. One way to improve Indonesia arbitration practice is by creating the jurisdiction as a friendly place to arbitrate, which firstly shall be analysed by reviewing its drawbacks as a preferable seat of arbitration, specifically on the procedure to enforce arbitral awards and the respective judicial supports to conduct arbitration within the jurisdiction.